2012
DOI: 10.1051/matecconf/20120205004
|View full text |Cite
|
Sign up to set email alerts
|

Corrélation entre la vitesse d’onde P et la conductivité thermique des matériaux hétérogènes et poreux

Abstract: Abstract. In the present study, the petrophysical properties of five different rocks have been measured and analyzed. This is the thermal conductivity, P-wave velocity and porosity. The methodology to estimate the thermal conductivity is to impose heat flux unidirectional on a sample and measure the temperature difference across the sample. The ultrasonic testing is based on the measurement of propagation time of a P-wave in the longitudinal direction. The porosity is measured by the mercury porosimetry techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…These results are consistent with literature results [7,16]. In general, we observe that the high value of the P-wave velocity is obtained for the samples saturated and the low value is obtained for dry samples.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with literature results [7,16]. In general, we observe that the high value of the P-wave velocity is obtained for the samples saturated and the low value is obtained for dry samples.…”
Section: Resultssupporting
confidence: 93%
“…In general, we observe that the high value of the P-wave velocity is obtained for the samples saturated and the low value is obtained for dry samples. The authors Boulanouar et al [7], Guéguen et al [17] and Rahmouni et al [18] compared the velocities P-wave in dry and saturated with water. They generally observed that V P (dry) < V P (saturated).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained for the measurement of P-wave velocities of dry samples range from 3.56 to 3.8 km/s and [21,23]. In general, we observe that the high value of the P-wave velocity is obtained for the samples saturated and the low value is obtained for dry samples.…”
Section: Resultsmentioning
confidence: 66%
“…In general, we observe that the high value of the P-wave velocity is obtained for the samples saturated and the low value is obtained for dry samples. The authors Boulanouar et al [22,23], Kahraman [24], Gué-guen et al [25] and Oghenero [26] compared the velocities P-wave in dry and water saturated states. They observed generally that V P (dry) < V P (saturated).…”
Section: Resultsmentioning
confidence: 99%